2021
DOI: 10.1063/5.0064963
|View full text |Cite
|
Sign up to set email alerts
|

Activity coefficients of aqueous electrolytes from implicit-water molecular dynamics simulations

Abstract: We obtain activity coefficients in NaCl and KCl solutions from implicit-water molecular dynamics simulations, at 298.15 K and 1 bar, using two distinct approaches. In the first approach, we consider ions in a continuum with constant relative permittivity (ɛr) equal to that of pure water; in the other approach, we take into account the concentration-dependence of ɛr, as obtained from explicit-water simulations. Individual ion activity coefficients (IIACs) are calculated using gradual insertion of single ions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Mean ionic activity coefficients (MIACs) and solubilities have been typically obtained in simulations using variations of the thermodynamic integration technique. , The MIACswhich quantify deviations from ideal solution behaviorare obtained from the differences between chemical potentials at a finite concentration (μ) and at a standard state reference state (μ † ). We have recently demonstrated that a single ion insertion technique accompanied by a counteracting neutralizing background can provide significant insights into the behavior of individual ions , and have obtained individual ion activity coefficients (IIACs) in qualitative agreement with available experimental data. The IIACs reveal disparities between the properties of anions and cations in solution and describe in detail the interactions between ions and solvent molecules.…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…Mean ionic activity coefficients (MIACs) and solubilities have been typically obtained in simulations using variations of the thermodynamic integration technique. , The MIACswhich quantify deviations from ideal solution behaviorare obtained from the differences between chemical potentials at a finite concentration (μ) and at a standard state reference state (μ † ). We have recently demonstrated that a single ion insertion technique accompanied by a counteracting neutralizing background can provide significant insights into the behavior of individual ions , and have obtained individual ion activity coefficients (IIACs) in qualitative agreement with available experimental data. The IIACs reveal disparities between the properties of anions and cations in solution and describe in detail the interactions between ions and solvent molecules.…”
Section: Introductionmentioning
confidence: 61%
“…We did not pursue this formal extrapolation here, in order to limit the computational cost of the study, but have investigated system size effects at a single composition, as indicated at the end of the Results and Discussion section. For the MIACs, any neutralizing-background or finite-size effects are expected to be small based on our prior studies. , …”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations